IMMANENT FEATURES OF THE PHILOSOPHICAL-SUFI CREATIVITY OF ALISHER NAVOI (TAMADDUN NURI JURNALI, 2025)
This article examines the Sufi terminology used in the works of Navoi to express his innermost thoughts, spiritual state and mystical aspirations. His love lyrics, epics «The Language of Birds», «Farhad and Shirin», «Leyli and Majnun» and others are especially saturated with Sufi concepts. The work «Nasaim ul-muhabbat» is entirely devoted to Sufism, the life and work of great sheikhs. Along with the wide use of Sufi concepts, Navoi develops his own categorical apparatus, his own classification of terms, arranging these categories in a hierarchical sequence corresponding to his worldview and value systems.